The Impact of Business Education on Moral Judgment Competence: An Empirical Study - Desplaces, David E. (Journal of business ethics, 2007)
This study uses theories of moral reasoning and moral competence to investigate how university codes of ethics, perceptions of ethical culture, academic pressure from significant others, and ethics pedagogy are related to the moral development of students. Results suggest that ethical codes and student perceptions of such codes affect their perceptions of the ethical nature of the cultures within these institutions. In addition, faculty and student discussion of ethics in business courses is significantly and positively related to moral competence among students. Our results point to the need to further examine the connections among academic institutional structures, ethics pedagogy, and students’ moral development.